The effect of seabed properties on the receive beam pattern of a hydrophone located on the seafloor. - Parsons, Miles; Duncan, Alexander (The Australian Acoustical Society, 2011)
Multi-path interference is often considered when modelling propagation of underwater sounds from source to receiver. When close to, or on the seabed, a hydrophone receives the direct and bottom reflected signals at nearly identical times. The resulting interference leads to an effective receive beam pattern that depends not only on source and receiver position and water depth, but also on the seabed characteristics, which affect the phase and magnitude of the reflection coefficient. Numerical acoustic propagation models account for this phenomenon automatically, however; it is important that it be taken into account when received signals are used to carry out simple calculations of source levels of nearby sources based on spherical spreading. Australian waters lie above seabeds of greatly differing acoustic properties. Compressional and shear sound speeds and absorption properties for four bottom types (basalt, calcarenite, sand and silt) were used to model the effective receive beam pattern of a hydrophone located on the seafloor. Modelling was carried out for all four seabeds as well as a seabed comprising differing thicknesses of sand over a calcarenite half space. The effects of the resulting receive beam pattern on estimations of source levels and locations are discussed.